Relaciones estructurales de máximo contraste en laderas - Rico M. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
A study is made of aspects related to the structure of grassland communities occupying contrasted positions on slopes. Thirty slopes were chosen in the 'dehesa' zone of the province of Salamanca (Spain); in each, the communities occupying the most extreme high (export) and low (accumulation) positions were inventoried. The covering data matrix thus obtained (60 communities x 185 species) was analysed by the Shannon Weaver index. Regarding the alpha diversity, significant differences were found in the structure of the communities occupying the low and high positions, the latter proving to be more diversified in all cases. These differences were reduced considerably on considering the gamma diversity. Overall, the communities present in the zones of accumulation reach a greater degree of heterogeneity than the export zones. The heterogeneity value attributable to topography is lower than those obtained from the set of communities situated on the high and low parts of the hill sides separately.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)